Synthesis of 11-(Piperazin-1-yl)-5H-dibenzo[b,e] [1,4]diazepine on Kilo Scale - Rahul S. Kalhapure; Bhushan P. Patil; Mahantesh N. Jadhav; Laxmikant A. Kawle; Sanjay B. Wagh (E-Journal of Chemistry)
A synthesis of 11-(piperazin-1yl)-5 H-dibenzo[b,e][1,4]diazepine on kilo scale without any chromatographic purification step is reported. Key steps involved are Ullmann condensation, catalytic hydrogenation, and catalyzed cyclization.